Current state of natural thickets of Glycyrrhiza glabra L. in Karakalpakstan (Experimental biology, 2015)
Data on geography, climate, soils and current state of natural thickets of a glycyrrhiza of the naked Republic of Karakalpakstan are provided in article in the territory. Data on researchers and the research works which were taking place earlier are specified. Comparative data on changes of populations of a glycyrrhiza naked, occurred for previous30 summer period are provided. Information on a chemical composition, application is also provided in scientific and national medicine, resources, places of trade thickets. Recommendations for the procuring organizations and collectors on rational collecting raw materials, and also necessary actions for preservation of populations of this valuable species of a plant are made.
Keywords: Karakalpakstan; Glycyrrhiza glabr; application; chemical composition; resources.